Real-time Prediction in Hands-free Computing for Disabled - Pradeep V (CLEI Electronic Journal)
For those with movement disabilities, a variety of hands-free mouse replacement systems have been developed, and during the past three decades, numerous advancements have been made. Over the past three decades, numerous authors have proposed alternatives to the mouse for people in the movement with disabilities who have not yet had a fair opportunity to utilise the standard input methods of a personal computer. In camera-based systems, the overhead of using head-mounted devices is reduced by using the web camera as the mouse. Tracking user facial expressions as they are being captured by the camera and accurately translating them into mouse cursor movement and click events are research challenges and opportunities. The current systems can only move the pointer in a slanting manner due to the user's accidental head movements losing the tracked feature. The movement has not yet allowed people with impairments the same chances as others to interact with computers. They have trouble using the input devices on computers due to their mobility problems. Controlling mouse pointer navigation is still difficult, despite the fact that on-screen virtual keyboards may be used to simulate a physical keyboard and speech recognition can be easily utilized to map mouse click events. The development of hands-free mouse replacement technologies has undergone much advancement. There are a number of limitations to mouse replacement systems that use a webcam as a mouse. In order to enable people with movement disabilities to use a standard PC, this research suggests enhancing the ability of camera-based hands-free computing systems to control the mouse cursor by predicting the user's selection of the target item in the GUI-based system using neural network techniques. Using samples where the mouse cursors predicted position values are closer to the user's actual selection region on the computer screen, the system is put to the test, and the anticipated outcome is achieved in every sample.